TEACHER IN OVERCOMING STUDENTS LEARNING DIFICULT MATHEMATHIC IN CLASS IV ELEMENTARY ISLAMIC CENTER UKHUWAH BANJARMASIN - hasanah, Noor (Jurnal PTK dan Pendidikan, 2016)
This research uses descriptive method is to determine the problem and solve it based on the data, presenting data, and analyze it. The population in this study were all fourth grade students SDIT Ukhuwwat Banjarmasin and selected samples are class IV-A and IV-B classes totaling 72 students. In collecting the data, the technique used is interview, observation and documentation.The research found that the difficulties experienced by students that have difficulty completing a different matter with the sample questions provided by the teacher on word problems, difficulty recalling the formula, and the difficulty in calculating operations multiplication and division problems. Efforts of teachers in addressing students' mathematics learning disabilities that provides the motivation to learn, give variety of teaching methods, use of props, provide adequate exercise and repetitive, and provide repair or remedial program.                                                                                          Keywords: difficulty learning math, math teacher